Internationalization of Multinational Companies and Cognitive Differences Across Cultures: A Neuroeconomic Perspective - Cheng, Huifang; Agbanyo, George Kwame; Zhu, Tianlun; Pan, HuiHong (Frontiers in Psychology, 2022)
From a classical perspective, MNCs operate based on market determinants, but recent economic discussions emphasize on the central role of the human cognitive system in the decision-making process, thereby given birth to interdisciplinary fields like behavioral economics and neuroeconomics. While neuroeconomics is still considered as an emerging field, hitherto scant studies have investigated the reflection of cultural experiences on the nervous system. Moreover, the interpretation of cultural diversity in the decision-making process, especially from a neuroeconomic perspective has not been explored. In response, this paper, a perspective research in nature, endeavors to research the neural responses to cultural diversity by contextualizing the neuroeconomic discussion within a MNC framework, as one of the best multicultural setting. This article demonstrates that the internationalization process of MNCs is established on the cultural identity and integration of the executive. Through a neuroscientific lens, our findings prove that culture is a fundamental determinant of the cognitive make-up, therefore cultural diversity in MNCs influences their decision-making process. Moreover, the performance of MNCs is driven by a cultural harmonization at the executive level. Lastly, the study reveals that, the novel field of neuroeconomics is instrumental in identifying cultural intuitions on brain cells and the implications on economic decisions even at a cooperate level. This main contribution of this paper is by initiating a multidisciplinary merge of the socio-cultural and economic and neuroscientific fields, as a research center for MNCs decision processes.